2013
DOI: 10.1186/1756-0500-6-135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Streptococcus pneumoniae adherence to human epithelial cells in vitro by the probiotic Lactobacillus rhamnosus GG

Abstract: BackgroundColonization of the nasopharynx by Streptococcus pneumoniae is considered a prerequisite for pneumococcal infections such as pneumonia and otitis media. Probiotic bacteria can influence disease outcomes through various mechanisms, including inhibition of pathogen colonization. Here, we examine the effect of the probiotic Lactobacillus rhamnosus GG (LGG) on S. pneumoniae colonization of human epithelial cells using an in vitro model. We investigated the effects of LGG administered before, at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…As described here, the assay does not distinguish between adherent and invasive (internalized) pneumococci. However, previous studies have found the levels of internalized pneumococci to be very small (typically ≤0.01% of inocula) 10 so for most isolates (including PMP843), the vast majority of cell-associated pneumococci are adherent rather than internalized. Additional applications include testing other probiotic species for the ability to inhibit colonization, and/or looking at mutant bacterial strains to investigate the role of specific genes of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described here, the assay does not distinguish between adherent and invasive (internalized) pneumococci. However, previous studies have found the levels of internalized pneumococci to be very small (typically ≤0.01% of inocula) 10 so for most isolates (including PMP843), the vast majority of cell-associated pneumococci are adherent rather than internalized. Additional applications include testing other probiotic species for the ability to inhibit colonization, and/or looking at mutant bacterial strains to investigate the role of specific genes of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro adherence assays have been used to examine pneumococcal adherence 8,9 . These assays have been adapted to investigate the impact of the probiotic Lactobacillus rhamnosus GG (LGG) on pneumococcal adherence 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms lead to the modulation of the microbiota and/or inhibition of colonization by potential pathogens, and bacterial translocation across the intestinal wall (Eizaguirre et al, 2011;Wine et al, 2009;Wong et al, 2013).…”
Section: Probioticsmentioning
confidence: 99%
“…Recent works have investigated the effect of probiotics on pathogen-mediated cytotoxicity in mammalian cells using the CFS approach (Wong et al, 2013;Bermudez-Brito et al, 2014). As the impact of an individual probiotic is influenced by the composition of the microbiota (Howarth & Wang, 2013), the present investigation included both CFS and CFSC.…”
Section: Cytotoxicity Of E Coli O157 : H7mentioning
confidence: 99%